Electronic Energy Transfer Modulation in a Dynamic Foldaxane: Proof‐of‐Principle of a Lifetime‐Based Conformation Probe. Issue 4 (11th December 2015) - Denisov, Sergey A.; Gan, Quan; Wang, Xiang; Scarpantonio, Luca; Ferrand, Yann; Kauffmann, Brice; Jonusauskas, Gediminas; Huc, Ivan; McClenaghan, Nathan D.
Abstract: Abiotic aromatic oligoamide foldamers are shown to self‐assemble in solution to form a double helix, which can accommodate a bichromophoric thread in its central void. While in solution reversible electronic energy transfer is instilled between chromophoric termini of the free, flexible thread as evidenced through delayed luminescence, upon rigidification of the rod the chromophores are mutually distanced and effectively decoupled. Consequently, the chromophores display their individual photophysical characteristics. The observed conformation‐dependent changes of dynamic luminescence properties, which are particularly sensitive to distance, offers a new strategy for lifetime‐based detection of geometry on the molecular scale as demonstrated through real‐time luminescence detection of molecular complexation leading to foldaxane formation. Abstract : A supramolecular abiotic double helix interpenetrated by a bichromophoric thread is described. While reversible interchromophore electronic energy transfer occurs in the excited free thread, giving prolonged emission, luminescence lifetime shortens when decoupled in the complex. The high sensitivity of emission decay to distance offers an approach to luminescence lifetime‐based conformational probes.